Delayed inpatient rehabilitation and functional outcomes for acute stroke: a retrospective cohort study in an Australian regional hospital - Fan He; Irene Blackberry; Michael Njovu; David Rutherford; George Mnatzaganian (Journal of Rehabilitation Medicine)
Background: The impact of delayed inpatient rehabilitation on the functional outcomes of stroke patients has not been reported in regional Australia.